Editorial note: Welcome to the year 2022 and Volume 25 - Assounga, Alain G (African Journal of Nephrology, 2022)
The Editorial Board and Editors of the African Journal of Nephrology wish all authors, reviewers and readers a very happy and blessed New Year. Like the last two years, we start this year in a wave of the COVID-19 pandemic. Hopefully, the future waves will be less and less severe and deadly. Given the significant protection against severe forms of disease provided by COVID vaccines, we urge everyone to get vaccinated. We are proud to announce that the African Journal of Nephrology is 25 years old this year. From its humble beginnings in 1997 when the founding editor-in-chief, the late Prof Maher Ramzy of Egypt, published the first i ssue, the Journal has persevered for 25 years and is now an established online publication and a member of the Directory of Open Access Journals. In 2021, the African nephrology calendar included the African Association of Nephrology (AFRAN) congress in Abidjan, Côte D’Ivoire, in December 2021. The pre-congress workshops included a workshop on research methodology organized with the collaboration of the ERA-EDTA Registry and the African Journal of Nephrology. The congress was successful despite the challenges of the pandemic, showcasing research from the continent. The proceedings will be published in volume 25 of the Journal. To commemorate our 25th year, we will continue with the African nephrology legacy project to document the history of nephrology in Africa. This volume will feature the history of nephrology in South Africa. The first publication of the African nephrology legacy project covered the history of AFRAN [1] and was published in 2017, authored by Prof Rashad Barsoum, the first AFRAN president. This year also marks the 10th anniversary of my tenure as Editor-in-Chief of the Journal. I am proud and honoured to have led the Journal for a decade. I wish to thank everyone who made it possible, including authors, reviewers and especially the editorial team including Deputy Editor Prof Razeen Davids, Associate Editors Prof Fergus Caskey, Prof Sarala Naicker and Prof Faiçal Jarraya, and Editorial Fellows Drs Yazied Chothia, Elliot Tannor and Vincent Boima. My thanks also goes to the secretarial team including Yolisa Mncundza, Jane John, Lethisha Harilall and the Turners Secretariat, the production team including Reach Publishers, Graham Baker and Ilze de Kock, Stellenbosch University for hosting the Journal, and the University of KwaZulu-Natal for supporting my efforts to lead the Journal and contribute to the promotion of African scholarship. Finally, in 2022, the South African Renal Congress will be held in Durban from 26–29 May and I invite you all to join us. Once again, Happy 25th Anniversary to the African Journal of Nephrology! Alain G Assounga Editor-in-Chief